Factors affecting mortality rate of Tagger goats in the Gezira State, Sudan - E. Elimam, Mohmed (Gezira Journal of Agricultural Science; Vol 10 No 2 (2012), 2023)
SHORT NOTE Goat meat is important in the Sudan due to high goat population, wide distribution and cheap prices. However, it is generally less preferred than mutton and beef and is preferred in rural areas. The international demand for goat meat is increasing due to its high nutritive value and low fat. However, exports are less than expected from goat population in the country. Goat meat production is still traditional in the Sudan and is based on natural pastures with low inputs and outputs (Mudawi, 2002; Ombabi and Elimam, 2007). Improving goat production is likely to boost local demand and exports and increase sheep and cattle exports. Goat meat production could be improved by improving health, genetic constitution, nutrition, management, marketing and capacity building. Tagger goat is mainly found in the Nuba Mountains, South Kordofan State, Sudan and is an important meat producer due to superior meat quality and conformation (Mofarrah, 1995; Elbukhary, 1998; Mudawi, 2002).The breed is recently introduced into the Gezira State for meat production. Mortality rate is among the main factors affecting goat meat production in the Sudan. Information on Tagger mortality rate is not available in the Gezira State. Consequently, this study was conducted to study Tagger mortality rates and factors affecting them in the Gezira State, Sudan.